Relationship Of Motor Ability With Skills Dribbling - Marta, Ibnu Andli; Kibadra, Kibadra; Yulifri, Yulifri (Yayasan Sekora, 2018)
The problem in this research is the low dribbling skills of soccer for the students of the UNP Laboratory Development Middle School. The purpose of this study was to determine the relationship between motor skills and dribbling skills. This type of research is correlational. The population is all students who take part in football extracurricular activities totaling 20 people. The entire population is sampled. Data were collected by measuring the two variables, ability and skill to dribble. Data were analyzed using product moment correlation. Based on the results of the study, the conclusion is that motor skills are significantly related (meaning) to the skills of dribbling at the UNP Laboratory Development Middle School students, because rcount 0.553> r table 0.444 and motor skills contribute 30.58% to dribbling skills.